Membumikan Al-Quran Dalam Etika Santri Kepada Kyai; Studi Tafsir Q.S Al Kahfi Ayat 66 – 70 - Nazilatus Syukriyah (Nazhruna: Jurnal Pendidikan Islam, 2019)
The ethics in educational process occupies the most significant place in Islamic intellectual tradition. One of the greatest Islamic education’s forms in Indonesia is Pesantren so its success signifies the success of this nation. The ethics between Santri (Pesantren’s learner) and Kyai (Pesantren’s lecture) is the identical tenet there, so it’s necessary to explore it in Al-Quran as our way of life. Hereby this study is purposed to obtain a deep understanding about the ethics of santri to Kyai by analyzing the interpretation of Al Kahfi verse 66 – 70. This is a qualitative research using literature method (library research) with the book Mafatih al-Gaib, written by Fahrudin Al – Razi, as the primer data source and the other related literature data as the secondary source. This study found that there are 10 ethical values in Al Kahfi verse 66 – 70 associated with the ethics of santri to Kyai i.e : a. Tawadlu’, b. Asking permition to study, c. feeling more stupid d. asking the kyai to teach e. believing that Allah gives the more knowledge for Kyai, f. Tawakkal and asking Allah’s guidance, g. studying seriously, h. absolute obedience, i. khidmah and j. doesn’t ask the other but knowledge.